Exercise and Smoking - Zourbanos, Νικόλαος; Theodorakis, Γιάννης (Inquiries in Physical Education and Sport, 2016)
Smoking is one of the main factors of morbidity worldwide. On the other hand, the benefits of physical activity in both physical and mental health have been known for many years. The purpose of this article is to present concisely the most important findings of a series of studies carried out under the program Thales – ESCAPEE, which was partly financed by Greece and the European Union. In general, the program Thales - ESCAPEE examined whether different exercise intensities (self-defined, moderate, high), in combination with selfregulation strategies, could help people who smoke to reduce or quit smoking. Our findings revealed that the development and implementation of a training program, within the framework of self-determination theory, in conjunction with self-regulation strategies, maybe beneficial for exercise adherence and smoking cessation.